2019
DOI: 10.18352/ijc.864
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Combining the IAD and SES Frameworks

Abstract: Elinor Ostrom's IAD (Institutional Analysis and Development) and SES (Social-Ecological Systems) frameworks are widely used by social scientists and policy analysts, but many applications fail to take full advantage of the potential utility of either framework. The IAD framework lacks detail regarding the specific variables that influence social interactions and neglects questions of asymmetric power and collective evaluation. The SES framework, meanwhile, supports detailed variable-oriented analyses of social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 52 publications
0
77
0
5
Order By: Relevance
“…;Hess 2012;McGinnis and Ostrom 2014;Cole et al 2019). The IAD/SES framework was used here as a diagnostic guideline to analyze the formal and informal rules-in-use within the PWBG groups and the political and institutional context framing their action arenas(Ostrom and Cox 2010;Ostrom and Basurto 2011).Figure 3summarizes the main components of an IAD/SES diagnostic…”
mentioning
confidence: 99%
“…;Hess 2012;McGinnis and Ostrom 2014;Cole et al 2019). The IAD/SES framework was used here as a diagnostic guideline to analyze the formal and informal rules-in-use within the PWBG groups and the political and institutional context framing their action arenas(Ostrom and Cox 2010;Ostrom and Basurto 2011).Figure 3summarizes the main components of an IAD/SES diagnostic…”
mentioning
confidence: 99%
“…Ostrom's SES framework was originally developed to study local common pool resources in relatively small-scale (largely rural) settings. It has subsequently been modified to study a wide variety of sustainability problems [14]. We found that, although its structure was broadly useful, we needed to modify it to be meaningful and relevant for large metropolitan settings.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…In order to systematically study the plurality of conditions and modes of governance in our study cities, we draw on the SES framework suggested by Ostrom and colleagues [12,13]. Ostrom's SES framework consists of a set of core subsystems relating to the social and ecological dimensions, with associated variables organized within a multilevel, nested structure This nested structure supports finely grained analyses of social and ecological conditions, which is the chief strength of the SES framework [14]. The work by Ostrom and her colleagues shows how this framework can be used to integrate concepts and theories across different disciplines and to organize research from disparate empirical settings [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To consider the temporal dynamics of land-use changes, we trace the actor interactions and their outcomes over the whole time period of the observed changes. By doing so, we distinguish two key phases of different context conditions: the time of the military government and the time after the transition to the new (semi-)civilian government starting in 2011/12 (Cole et al 2019). 1…”
Section: Conceptual Frameworkmentioning
confidence: 99%